Assessment of Sugarcane Byproducts for Energy Use in Peru - Marcelo D. (2017)
The scope of this paper is to make a feasibility analysis for energy production from sugarcane byproducts in Perú. Therefore, it is shown the history, methods, current scenario and future prospects of sugarcane plantations related to the ethanol industry and the sugar industry. There will be shown analysis of harvest residues (top and leaves). Bagasse is a mill residue, produced after sugarcane juice is extracted from the sugarcane. Nowadays this residue is burnt in boilers and this energy is used to generate steam. In the other hand, harvest residues represent a significant part of the energy contained in the sugarcane, but it is left in the field, or worse; burnt before the harvest. There will also be shown an estimated value of the electricity generation potential from sugarcane residues.